ANALISIS LINIERITAS PELAKSANAAN PSG TAHUN 2011 DI LEMBAGA MITRA BAGI SISWA PROGRAM KEAHLIAN AKUNTANSI DI SMKN 2 KEDIRI TAHUN 2012 - Meta Ardiana, (Pendidikan Ekonomi, 2012)
PSG is a real step to make vocational education and training system is more linear with the needs of the working world. But the reality shows in the implementation of PSG have not found a match between the job of accounting expertise obtained during the implementation of PSG students in partner institutions. This study was to analyze how the implementation of PSG at SMK N 2 Kediri. This research using descriptive analysis techniques, and the data used are the primary data and secondary data. These results indicate that the procedures for implementing Multiple System of Education (PSG) in SMK Negeri 2 Kediri is PSG in accordance with the criteria PSG.